THE HIDDEN CURRICULUM AND SPIRITUAL INTELLIGENCE OF ALPHA GENERATION STUDENTS AT THE ARRAUDLAH ISLAMIC BOARDING SCHOOL - Dini Nur Islami; Ahmad Miftahul Ma’arif (Universitas Kiai Abdullah Faqih Gresik, 2026)
Generation Alpha is a generation born and raised in the digital era, facing significant challenges in spiritual development due to their intense exposure to technology. Islamic boarding schools (pesantren) as institutions of Islamic education hold a strategic role in nurturing the moral and spiritual dimensions of students through the hidden curriculum an unwritten form of education instilled through institutional culture, habits, and social interaction. This study employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The aim of this research is to analyze the implementation of the hidden curriculum in strengthening the spiritual intelligence of Generation Alpha students and to identify which aspects of spiritual intelligence are reinforced through such implementation. The findings reveal that the hidden curriculum is implemented through intensive communication among pesantren members, utilization of available resources including facilities and educators, the exemplary conduct of ustadz/ustadzah, and a supportive bureaucratic structure. The spiritual intelligence aspects strengthened include forgiveness, sincerity (ikhlas), consistency (istiqomah), calmness, promptness in completing tasks, and sensitivity toward others.